STRATEGIC COGNITION AS MICROFOUNDATIONAL MEDIATOR OF INNOVATION COMMERCIALIZATION PERFORMANCE - Hana Timoti; Henry Eryanto; Agus Wibowo (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
This paper develops a microfoundational explanation of innovation commercialization by positioning Strategic Cognition (SC) as the cognitive mechanism through which organizational capabilities are transformed into sustained commercialization outcomes in the Indonesian oil and gas industry. The study addresses an unresolved empirical finding from prior research in this program, theoretically unexplained until now. Drawing on a PRISMA-based systematic literature review of 68 high-quality studies published between 2015 and 2025, the paper identifies a theoretical tension between Dynamic Capabilities Theory, which implies a direct capability-to-performance relationship, and the microfoundations perspective, which emphasizes cognitive mediation. To reconcile this tension, the study theorizes that Strategic Cognition, operating through its three cognitive mechanisms, transforms Internal Dynamic Capability (IDC) and Innovation Ecosystem Quality (IEQ) into Technology Commercialization Capability (TCC), which subsequently drives Sustained Innovation Commercialization Performance (SICP). The proposed framework specifies two serial mediation pathways (IDC → SC → TCC → SICP and IEQ → SC → TCC → SICP). By integrating dynamic capabilities and microfoundational perspectives, the study extends commercialization theory for long-cycle, highly regulated industries, clarifies the capability–performance relationship, identifies the missing cognitive mechanism underlying commercialization capability formation, and offers a theoretically grounded framework for managing innovation commercialization in the oil and gas industry.